Penguatan Otonomi Desa Adat melalui Pendampingan Penyusunan Awig-awig Sekaa Teruna-Teruni di Banjar Luglug, Desa Adat Lembeng, Kabupaten Gianyar - Sudharma, I Made (Sevanam: Jurnal Pengabdian Masyarakat, 2026)
This article examines the legal standing of the Sekaa Teruna-Teruni awig-awig within the framework of customary village autonomy under Article 18B of the 1945 Constitution and applicable legislation, particularly Bali Provincial Regulation No. 4 of 2019 on Customary Villages in Bali. Furthermore, this article describes the process of assisting in the drafting of the awig-awig of Sekaa Teruna-Teruni Dharma Laksana in Banjar Luglug, Desa Adat Lembeng, Gianyar Regency as a concrete manifestation of strengthening customary village autonomy in local governance based on customary law. This research employs a juridical-empirical method through observation, in-depth interviews, and documentary studies. The results indicate that the Sekaa Teruna-Teruni awig-awig holds a strong legal position as state-recognized customary law and serves as a vital instrument for Balinese youth to self-organize independently. The drafting assistance process contributes significantly to strengthening customary village institutional capacity, preserving local wisdom values, and increasing the active participation of youth in customary village governance. This research recommends that similar assistance be extended to all banjar across Bali as a sustainable strategy for strengthening customary village autonomy.